Attractive Visuality Generation Within the 360˚-VR Video Format as a Technological Trend in Modern Film Production - Pecheranskyi, Ihor (Kulʹtura ì mistectvo u sučasnomu svìtì (Online), 2023)
The aim of the article is to study the features of the process of attractive visuality generation within the 360˚-VR video format. Results. A comprehensive consideration of the issue with the use of general scientific and special methods (problem-logical, theoretical-informational, art studies, comparative analysis, the method of analogy, abstraction, induction, and deduction) demonstrates that one of the key trends in modern film production is the creation of a “multinarrative space” (A. G. Iñárritu) VR-immersion of the viewer as a recipient and co-creator of this space, accompanied by the transformation of the film into a visually attractive activity and transformation principles of film aesthetics in the 20th century. Scientific novelty. It is proved that the 360˚-VR video format is a unique audiovisual form that requires a special grammatical, technical and technological base (professional or amateur 360˚ camera, effective tools for creating and editing 360˚video content for the different platforms, Kolor Autopano Video Pro, SIFT algorithm, etc.) thus, brings the use of the immersion principle to a qualitatively new level. Conclusions. Due to this, attractive visuality is becoming possible in the quality of a new aesthetic and perceptual-virtual experience that is being formed under the influence of VR-attractions and modern special effects in the digital cinematograph. It leads to the synthesis between cinematograph and theatre when the transition is occurring from montage sequence to virtual-theatrical play where in consequence of 360˚-VR the action has been developing constantly, and the viewer is in the very centre of the events. Thereby, there are grounds to confirm that, including technological development and measureless creative possibilities in the process of projecting different VR-attractions, it is possible for a viewer’s infinite immersion in the space of a digital film; that, from one side, transforms film language on the modern stage, creating the perspectives of the further branch development, and from another side, it conditions a number of psychological problems and risks connected with the viewers’ reaction on a different level of density of the attractive field of modified film language. Мета статті — дослідити специфіку процесу генерування атракційної візуальності у форматі 360˚-VR відео. Результати дослідження. Під час комплексного розгляду проблеми із застосуванням загальнонаукових і спеціальних методів (проблемно- логічного, теоретико-інформаційного, мистецтвознавчого, порівняльного аналізу, методу аналогії, абстракції, індукції та дедукції) доведено, що одним із ключових напрямів у сучасному кіновиробництві є створення «мультинаративного простору» (А. Г. Іньярріту) VR-занурення глядача як реципієнта та співтворця цього простору, що супроводжується трансформацією фільму у візуально привабливу діяльність з урахуванням принципів кіноестетики ХХ ст. Наукова новизна. Доведено, що формат відео 360˚-VR є унікальною аудіовізуальною формою, яка потребує спеціальної граматичної та техніко-технологічної бази (професійна або аматорська 360˚ камера, ефективні інструменти для створення та редагування 360˚ відеоконтенту для різних платформ, Kolor Autopano Video Pro, алгоритм SIFT та ін.), та виводить використання принципу занурення на якісно новий рівень. Висновки. Атракційна візуальність стає можливою як новий естетичний і перцептивно- віртуальний досвід, що формується під впливом VR-атракцій і сучасних спецефектів у цифровому кінематографі. Це призводить до синтезу кінематографа і театру, коли відбувається перехід від монтажної послідовності до віртуально-театральної гри, де завдяки 360°-VR дія постійно розвивається, а глядач перебуває в центрі подій. Отже, технологічний розвиток і безмежні творчі можливості в процесі проєктування різних VR-атракцій сприяють нескінченному зануренню глядача в простір цифрового фільму, що, з одного боку, трансформує кіномову на сучасній сцені, створюючи перспективи подальшого розвитку галузі, а з іншого — зумовлює низку психологічних проблем і ризиків, пов’язаних із реакцією глядачів на різний рівень щільності атрактивного поля модифікованої кіномови.